Preference of Japanese Global Health Personnel—Lessons Learned from a Qualitative Study - Sugishita, Tomohiko; Jibiki, Eriko (Kokusai Hoken Iryo (Journal of International Health), 2021)
Objectives  The need to develop and produce human resources for global health is increasing. The objective of this study was to reveal through qualitative research as a first step of Discrete Choice Experiment, which job ‘attributes’ are considered important by Japanese medical and non-medical personnel in considering employment at health-related international organizations. We then sought to identify appropriate support measures that match the chosen attributes for those who wish to work for international organizations. Methods  We requested a total of 20 subjects from 3 groups of Japanese medical and non-medical personnel; 1. those who wish to work for health-related international organizations (applicant group), 2. those who are currently working (working group) and, 3. those who resigned (resigned group).   Subjects were asked to choose and rank in order of importance, 11 pre-defined attributes when considering employment at international organizations, followed by semi-structured interviews.Results  All three groups chose job content, opportunity for self-realization and opportunity for capacity development as top three attributes. This was followed by duty station as second place tie for working group and fourth place for applicant and resigned groups.   However, for applicant and working groups, emphasis on employee’s entitlements such as work-life-balance, salary, welfare, job security/long-term contract ranked mid- to lower-level between fifth to eighth places. Guaranteed job where one can return to when one leaves the current post, ranked ninth place and opportunity for children’s education and opportunity for spouse’s job ranked tenth equally.   For the resigned group, work-life-balance and job security/long-term contract ranked fifth place equally but other attributes were not chosen.Conclusion  The study findings suggested that Japanese medical and non-medical personnel who aim for employment at health-related international organizations have tendencies to opt for utilization of their experiences and expertise, and search for capacity development and self-realization, rather than better employee entitlements or working/living conditions.   According to the attributes ranking, we consider implementation of career development seminars on expected job satisfaction at international organizations as the primary support measure to encourage and dispatch more personnel. However, publicity highlighting employee entitlements such as work-life-balance, working environment for women and welfare alongside salary may also provide better incentive.   Insecure contract terms, a lack of national organizations and hospitals that value the experience gained in international organizations present a challenge. There is a need to work with these organizations in the mid- to long-term to inform them on the benefits of accepting those staff wishing to return after a period working within international organizations.